Relationship between nurses' practice environments and nursing outcomes in Turkey. - Topçu, I; Türkmen, E; Badır, A; Göktepe, N; Miral, M; Albayrak, S; Kebapçı, A; Serbest, Ş; Özcan, D (My University, 2016)
This study aimed to understand nursing practice environment characteristics in Istanbul-area hospitals in Turkey, the relationship between these characteristics, nurse burnout levels and nurses' intentions to leave work.

A well-known relationship exists in many countries between nursing practice environments and nurse burnout and intention to leave work. However, little is known about the relationship between practice environment characteristics and nursing outcomes in Turkey.

This cross-sectional study was conducted among 2592 nurses in 20 Ministry of Health and 29 private hospitals in Istanbul, Turkey. A demographic questionnaire, Practice Environment Scale of the Nursing Work Index and Maslach Burnout Inventory were used for data collection.

Almost half of nurses suffered from high-level burnout related to emotional exhaustion and personal accomplishment, and one-third reported depersonalization and the intent to leave their jobs within a year. A poor nursing practice environment was the leading factor, increasing nurses' burnout levels in all subdimensions. Burnout related to emotional exhaustion, personal accomplishment and poor practice environment increased intention to leave. Permanent positions decreased intention.

There was a relationship between poor practice environments and nursing outcomes in Turkey.

The use of a survey data collection method is a potential study limitation. Quantitative and qualitative methods could be combined to obtain more detailed objective data about nursing practice environments.

Poor practice environments, high-level burnout and intention to leave work are significant problems in Istanbul, Turkey. Favourable practice environments and job security should be provided to improve nursing outcomes.

Policymakers and nurse managers should be aware of any negative issues regarding nursing practice environments and job security to improve nursing outcomes.
Keywords: Burnout; Intention to Leave Work; Nursing Work Index; Practice Environment; Turkey